1995
DOI: 10.1111/j.1365-2338.1995.tb01119.x
|View full text |Cite
|
Sign up to set email alerts
|

Plant quarantine significance of dwarf bunt of wheat to China

Abstract: The adaptability of Tilletia controversa was studied in particular relation to China, where wheat is cultivated under various climatic conditions. Teliospore germination is closely influenced by temperature, light and soil humidity. Establishment of T. controversa depends on: (1) persistent low temperature (0–10°C) within the surface layer of the soil, in combination with adequate soil moisture; (2) presence of seedlings of susceptible wheat cultivars, especially in the early stage of tillering before or durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Johnsson (1992) suggested that both low temperatures during autumn and persistent snow cover during winter were associated with high incidence of dwarf bunt. Cloud cover may contribute to infection of dwarf bunt during winter (Zhang et al 1995).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Johnsson (1992) suggested that both low temperatures during autumn and persistent snow cover during winter were associated with high incidence of dwarf bunt. Cloud cover may contribute to infection of dwarf bunt during winter (Zhang et al 1995).…”
Section: Methodsmentioning
confidence: 99%
“…where N C [0, 1] represents monthly frequency of clouds with visible optical depths > 6 and where f is a correction factor. Zhang et al (1995) reported that in China about 5% of wheat was infected by dwarf bunt under cloud cover conditions, whereas Hoffmann (1982) reported that about 60% of susceptible cultivars were infected under persistent snow cover. In the present study, the value of f was assumed to be 0.08 at first.…”
Section: Methodsmentioning
confidence: 99%